2014
DOI: 10.5301/hipint.5000131
|View full text |Cite
|
Sign up to set email alerts
|

Hip Muscle Strength Recovery after Hip Arthroscopy in a Series of Patients with Symptomatic Femoroacetabular Impingement

Abstract: Patients with symptomatic FAI recovered their hip muscle strength to normal levels 2.5 years after hip arthroscopy, except for hip flexors. Although all patients showed good hip muscle strength at follow-up, half of them were not completely satisfied with their health state related to the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
2
32
0
2
Order By: Relevance
“…All studies included participants based on a diagnosis of FAI and associated labral and/or chondral pathology. The method of diagnoses ranged from arthroscopic findings,22 23 27 28 to positive clinical signs on physical examination,24 26 29–33 to radiographic, CT or MRI diagnosis 3 24–26 29–32 34–38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies included participants based on a diagnosis of FAI and associated labral and/or chondral pathology. The method of diagnoses ranged from arthroscopic findings,22 23 27 28 to positive clinical signs on physical examination,24 26 29–33 to radiographic, CT or MRI diagnosis 3 24–26 29–32 34–38…”
Section: Resultsmentioning
confidence: 99%
“…Physical impairment outcomes reported included hip joint ROM;3 22 23 25 27 33 34 36 37 39–42 hip muscle function;22 26 29 30 31 33 simulated hip joint ROM using three-dimensional CT or three-dimensional kinematics;24 28 32 34 38 43 hip muscle volume;31 hip muscle EMG;29 30 and functional performance tasks such as single leg balance,27 squat depth and pelvic ROM,44 and number of strides per day 35. The reliability of physical impairment outcomes measured was reported in 7 out of the 23 studies.…”
Section: Resultsmentioning
confidence: 99%
“…AIIS avulsions, which include the origin of the rectus femoris, have been reported to result in hip flexor and knee extensor strength deficits [10]. A recent study has shown that hip flexor muscle strength is decreased after arthroscopic FAI surgery [3]. If an overly aggressive resection of the AIIS is performed, the direct head of the rectus femoris could potentially be partially or completely detached from its origin (AIIS), and this could result in potential hip flexor and knee extensor strength deficits.…”
Section: Discussionmentioning
confidence: 99%
“…A priori power analysis was performed using G* power 3 under the following conditions (paired t test, power 0.8, significance level p = 0.05) [3]. The results of this analysis were effect size d = 0.75, total sample size = 17, and actual power = 0.81.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation